Unveiling the powerhouse: Exploring the dynamic relationship between globalization, urbanization, and economic growth in Bangladesh through an innovative ARDL approach (Lighthouse Publishing, 2023)
Significant changes in the economic landscape of Bangladesh have occurred in recent decades due to variables such as globalization, urbanization, FDI, trade, population dynamics, and their interplay. Effective policies and strategies must be developed with a thorough comprehension of the interconnected dynamics of these factors and their influence on economic expansion. This study investigates the dynamic linkages between globalization, urbanization, foreign direct investment (FDI), trade, population, and economic growth in Bangladesh. The study employs sophisticated econometric techniques to analyze the impact of these variables on the nation's economic landscape from 1991 to 2021. The stability of the dataset is evaluated using stationarity tests including ADF, DF-GLS, and P-P unit root tests. The results indicate a varied order of integration estimation for the investigated variables, necessitating additional investigation. The Autoregressive Distributed Lag (ARDL) estimation technique is utilized to investigate the long-term relationship between the variables. The results demonstrate a positive and statistically significant relationship between globalization, urbanization, trade, FDI, and economic growth. The significance of external factors and urbanization in propelling Bangladesh's economic growth is highlighted by these findings. Surprisingly, during the examined period, population dynamics had no significant impact on economic growth. This emphasizes the need for policymakers to investigate the intricate relationship between population trends and sustainable economic growth. Using the Ramsey Reset test, Jarque-Bera test, Breush Godfrey LM test, and CUSUM & CUSUM square test, the model's dependability is rigorously evaluated. The results demonstrate the model's robustness and validity, bolstering the veracity of the study's findings. On the basis of the research findings, a number of policy recommendations emerge. To promote economic growth, it is recommended that Bangladesh continue to embrace globalization, encourage FDI, and strengthen international trade relations. In addition, policymakers should prioritize urban development to capitalize on the economic benefits of urbanization. To address population dynamics, a balanced approach is required. To maximize the potential of the young workforce, population control measures should be considered alongside investments in education, skills training, and healthcare.